Respuesta :

Answer:

Multiply by 18

Step-by-step explanation:

Given

[tex]\frac{x}{3} + \frac{x}{6} = \frac{11}{9}[/tex]

Required

Eliminate the fraction

To eliminate the fraction, we first determine the LCM of the denominators (3, 6 and 9)

This is show below:

List out the multiplies of 3, 6 and 9

[tex]3 = 3,6,9,12,15,18,21,24,27,30...[/tex]

[tex]6 = 6,12,18,24,30...[/tex]

[tex]9 = 9,18,27...[/tex]

The least common multiple is 18.

Hence, when both sides of the equation is multiplied by 18, the fraction is eliminated;

See proof

[tex]18 * (\frac{x}{3} + \frac{x}{6}) = \frac{11}{9} * 18[/tex]

[tex]\frac{18x}{3} + \frac{18x}{6} = \frac{11*18}{9}[/tex]

[tex]6x + 3x = 11 * 2[/tex]

[tex]6x + 3x = 22[/tex]

The fraction is eliminated